Análisis de los valores geomorfológicos de interés y puesta en valor en el sector nororiental del futuro Parque Nacional de la Sierra de las Nieves - Martínez-Murillo, Juan Francisco (My University, 2018)
This study deals with the first approach to the analysis of geomorphological features from the future Sierra de las Nieves national park in order to inventory and value the main geomorphosites. This is done as follows: geomorphological characterization and mapping, inventory of geomorphosites, and valuation focussed on their scientific, cultural and management values. The study area sums remarkable geomorphosites to the values responsible of the future declaration in national park.
Analysis of the valuable geomorphological sites in the eastern sector from the future Sierra de las Nieves National Park
Keywords: Geomorfología; Parques Nacionales; Sierra de las Nieves; Lugares de ínterés geomorfológico (LIG)